Respuestas

  • Usuario de Brainly
2014-01-13T19:32:18+01:00
3x^2 +33x +90=0  simplifico dividiendo por 3
x^2 +11x +30=0 factorizo
(x +6 )(x *5) =0
x+6 =0
x= -6

x+5 =0
x=-5
solucion ( -6 , -5)

  • Usuario de Brainly
2014-01-13T19:33:23+01:00
3x² + 33x + 90 = 0

Simplificamos, para que sea más fácil calcularlo:
x² + 11x + 30 = 0          Divido todo entre 3

x =  \frac{-11 \frac{+}{}  \sqrt{11^2-4*1*30} }{2*1}

x =  \frac{-11 \frac{+}{}  \sqrt{121-120} }{2}

x =  \frac{-11 \frac{+}{}  \sqrt{1} }{2}

x =  \frac{-11 \frac{+}{}1}{2}

x₁ = (-11 + 1)/2 = -10/2 = -5
x₂ = (-11 - 1)/2 = -12/2 = -6

Solución:
x₁ = -5
x₂ = -6